Combined effects of sex hormone‐binding globulin and sex hormones on risk of incident type 2 diabetes: 性激素结合球蛋白与性激素联合预测2型糖尿病的发生. (1st September 2015) - Hu, Jinbo; Zhang, Aiping; Yang, Shumin; Wang, Yue; Goswami, Richa; Zhou, Huang; Zhang, Yi; Wang, Zhihong; Li, Rong; Cheng, Qingfeng; Zhen, Qianna; Li, Qifu
Abstract: Background: The aim of the present study was to investigate the combined effects of sex hormone‐binding globulin (SHBG) and sex hormones on the risk of type 2 diabetes (T2D). Methods: A nested case‐control study of Chinese participants in the Environment, Inflammation and Metabolic Diseases Study (2008–13) was performed. Of the 3510 subjects free of diabetes, 145 men and 87 women developed diabetes over the 5‐year follow‐up. One age‐ and sex‐matched control subject was selected for each case. Baseline concentrations of SHBG, estradiol, testosterone, and dehydroepiandrosterone sulfate (DHEA‐S) were divided into tertiles and subjects were classified as having low, intermediate and high levels accordingly. Results: After multivariate adjustment, men with low SHBG levels had a fourfold greater risk of T2D than men with high SHBG levels. Conversely, men with high estradiol levels had a fourfold greater risk of T2D than men with low estradiol levels. Men with low SHBG + high estradiol had a 20‐fold greater risk of T2D than men with high SHBG + low estradiol (odds ratio [OR] 20.23; 95% confidence interval [CI] 4.62–51.33). These risk associations in men were not observed for testosterone or DHEA‐S, alone or in combination with SHBG. Compared with low SHBG, the risk of T2D decreased with increasing SHBG tertile (OR 0.92 [95% CI 0.21–4.53], 0.14 [95% CI 0.10–0.74]; P trend  = 0.043) after multivariate adjustment in women. Estradiol, testosterone, and DHEA‐S levels showed no association with T2D in women. Conclusion: Low SHBG in conjunction with high estradiol has an additive detrimental effect on the risk of T2D in men.